2016
DOI: 10.2166/wh.2016.079
|View full text |Cite
|
Sign up to set email alerts
|

Household water insecurity is associated with a range of negative consequences among pregnant Kenyan women of mixed HIV status

Abstract: Water insecurity (WI) is a serious and worsening problem worldwide, but its role in health outcomes among people living with HIV or pregnant women is unknown. We assessed experiences of WI in a cohort of 323 pregnant Kenyan women of mixed HIV status. The majority (77.7%) had at least one experience of WI in the previous month; it was associated with negative economic, nutrition, disease, and psychosocial outcomes. A standardized cross-culturally valid household WI scale would facilitate assessment of the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 8 publications
3
50
0
Order By: Relevance
“…Women and men often have different knowledge or uses of water, and play different roles in procuring water or with respect to formal and informal water governance institutions (Harris, Kleiber, Goldin, Darkwah, & Morinville, ). Although it varies by context, women often play an important role in accessing water for domestic uses, and may travel long distances to fetch water and queue for long periods to procure water (Krumdieck et al, ; Singh, Jacks, Bhattacharya, & Gustafsson, ; Sorenson, Morssink, & Campos, ). In different cultural contexts, women are sometimes seen as “water keepers” who have specific roles and responsibilities to provide water, to maintain quality, or to engage in spiritual practices involving water (Anderson, Clow, & Haworth‐Brockman, , e.g., of Indigenous communities in Canada).…”
Section: Cross‐cutting Factors That Shape Water Sharingmentioning
confidence: 99%
“…Women and men often have different knowledge or uses of water, and play different roles in procuring water or with respect to formal and informal water governance institutions (Harris, Kleiber, Goldin, Darkwah, & Morinville, ). Although it varies by context, women often play an important role in accessing water for domestic uses, and may travel long distances to fetch water and queue for long periods to procure water (Krumdieck et al, ; Singh, Jacks, Bhattacharya, & Gustafsson, ; Sorenson, Morssink, & Campos, ). In different cultural contexts, women are sometimes seen as “water keepers” who have specific roles and responsibilities to provide water, to maintain quality, or to engage in spiritual practices involving water (Anderson, Clow, & Haworth‐Brockman, , e.g., of Indigenous communities in Canada).…”
Section: Cross‐cutting Factors That Shape Water Sharingmentioning
confidence: 99%
“…For example, low and intermediate water access was associated with higher blood pressure in women in both urban and rural Nepal, with the highest pressure associated with the lowest access (Brewis, Choudhary, & Wutich, 2019b). Limited water access has been found to be associated with increased anxiety, worry, stress, feelings of hopelessness, and arguments over water (Brewis, Choudhary, & Wutich, 2019a; Kangmennaang, Bisung, & Elliott, 2020; Krumdieck et al, 2016; Ženko & Menga, 2019). People with poor mental health in rural Malawi—in contrast to those with good mental health—perceived that the collection of safe water required time and effort and that it was therefore difficult to collect enough water; they also felt more vulnerable to disease from not collecting safe water (Slekiene & Mosler, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…By looking at responses across time, we were able to reduce the scale to only 20 questions using a series of statistical procedures. Although we have yet to investigate the relationships between water insecurity and health outcomes, formative work has revealed that 77.3 percent of our participants felt "somewhat or strongly concerned" for their physical safety during water acquisition; 64.1 percent reported drinking unsafe water; 65.3 percent reported worrying about accessing sufficient water; and women without water in their compound spent a mean of 4.5 (±6.7) hours per week acquiring water (Krumdieck et al 2016). These early findings underscore the fact that women disproportionately bear the burden of water insecurity, and that it has far-reaching consequences.…”
Section: In Focus Watermentioning
confidence: 89%